2012
DOI: 10.4136/ambi-agua.845
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de lâmpadas germicidas na desinfecção de esgoto sanitário

Abstract: RESUMOO objetivo deste estudo foi investigar a eficiência de lâmpadas germicidas no tratamento terciário de esgoto sanitário no controle de patógenos. O desempenho do reator fotoquímico utilizado nos ensaios foi monitorado em análises microbiológicas para quantificação de E. coli (indicador de bactérias), C. perfringens (indicador de protozoários) e colifagos (indicador de vírus). Os experimentos foram realizados com efluente proveniente de um reator UASB instalado na ETE-USP campus São Carlos submetido a um f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…It can be inferred that the best quality effluent resulted in even better efficiency in the UV doses applied with inactivation of the indicator organisms. Similar results are in line with other studies, despite not having ideal conditions of turbidity and COD, but also showing total coliform and E. coli inactivation (Bilotta and Daniel 2012 ; Medeiros and Daniel, 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…It can be inferred that the best quality effluent resulted in even better efficiency in the UV doses applied with inactivation of the indicator organisms. Similar results are in line with other studies, despite not having ideal conditions of turbidity and COD, but also showing total coliform and E. coli inactivation (Bilotta and Daniel 2012 ; Medeiros and Daniel, 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…For this result, the difference between the wastewater values of the Wetlands outlet and the UV outlet was analyzed (Table 2). Bilotta and Daniel (2012) tested the effect of effective UV doses (123.0 and 247.0 mWscm -2 ) on effluent from secondary treatment with exposure times of 60/120 seconds and noted the inactivation of 1.6 to 5.2 log-cycles of E. coli. Souza et al (2012) in one of their UV assays observed that 317.1 mWscm -2 were required to inactivate 3.7 and 2.0 log-cycles of E. coli and CT, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…O aumento da demanda por fontes de água para consumo humano e industrial, aliada ao comprometimento da qualidade da água dos mananciais de abastecimento, tem incentivado a busca por procedimentos mais adequados para reduzir a poluição dos recursos hídricos (BILOTTA, 2012), severamente degradados na maioria dos países, independente do nível de desenvolvimento.…”
unclassified